The Implementation of Maritime Diplomacy as Indonesia’s Effort to Counter Threats in the Exclusive Economic Zone - Alfarizi, Baqi Zaenulhaq; Bainus, Arry; Sudirman, Arifin (Journal of Public Representative and Society Provision, 2025)
As an archipelagic state, Indonesia possesses a strategic and resource-rich Exclusive Economic Zone (EEZ), yet remains vulnerable to sovereignty violations by foreign actors. These threats, particularly in the North Natuna Sea, have prompted the Indonesian government to implement maritime diplomacy as a non-military approach to safeguard its national interests. This article analyzes Indonesia’s implementation of maritime diplomacy in addressing unilateral claims by China and other threats within its EEZ. Using a qualitative approach and literature studies, the study highlights diplomatic strategies such as official protests, multilateral cooperation, defense diplomacy, and the development of border regions. The findings suggest that maritime diplomacy has been effective in reinforcing Indonesia’s legal position and international image, despite ongoing challenges in internal coordination and regional dynamics.